Board effectiveness and bank risk taking: a case of Malaysian banking institutions / Nur Hidayah Anuar - Anuar, Nur Hidayah (2014)
This study explored the relevance of corporate governance and extent of risk taking in banks. The main objective is to identify the relationship board effectiveness, as one of the elements of the internal mechanisms of corporate governance with bank risk taking. By using a sample of conventional and Islamic banks over the period of 2008 to 2012, this study measured board effectiveness by board size, board independence and financial expertise of independent directors. In order to measure bank risk taking, credit risk is used as it is deemed to be a major risk in the banking industry. In discussing the analysis of the result, this study explores the analysis from the perspective of agency theory in banking industry. Statistical findings from multiple regression analysis indicate that, out of three components of board effectiveness in this study, only board size and board independence significantly positively affect credit risk. This further implied that the existence of larger board size and high number of independent directors served on the board could serve the interest of bank’s shareholders who have preferences for ‘excessive risk’ in the presence of ‘moral hazard’ problem from limited liability and deposit insurance. Besides that, the disadvantages of having a larger board and large board independence could also contribute to significant positive relation to bank credit risk. These results remain robust having bank size, ownership structure and types of banks as control variables.